High sperm concentration during cryopreservation decreases post-thaw motility percentage without compromising in vitro fertilization outcomes in common carp - Sotnikov, Anatolii; Rodina, Marek; Stechkina, Taisiya; Benevente, Cristiane Fernanda [UNESP]; Gela, David; Boryshpolets, Sergii; Kholodnyy, Vitaliy; Linhart, Otomar; Dzyuba, Borys (Elsevier, 2023)
To avoid mechanical compression of spermatozoa during the cryopreservation, a high dilution ratio with the cryoprotective medium is applied. Due to this, the sample volume increases, which entails increased cryobank capacity. Moreover, the high volume of cryomedias does not allow to fertilize of large volumes of eggs in practical artificial reproduction of common carp aquaculture. The current study demonstrated that reasonable lowering of dilution rates might still be effective for carp sperm cryobanking —elevation of spermatozoa concentration up to 13 × 109 spz mL−1 resulted in a significant decrease in post-thaw sperm motility percentage to 20% compared with 39% in 0.5 × 109 spz mL−1. Nevertheless, no significant differences in sperm kinetic parameters (VCL and LIN) were found in this case. The fertilization outcome (embryo development and hatching rates) was similar after applying thawed sperm samples with “optimal” (2.2–2.4 × 109 spz mL−1) and “sub-optimal” (11.0–13.0 × 109 spz mL−1) concentrations (sperm/egg ratio at fertilization was in the range of 0.3–4.5 × 105 spz/egg). Thus, applying a low dilution rate such as one part of sperm to one of the cryoprotective mediums is favorable for decreasing cryo-storage space and the sperm volume needed to fertilize big egg numbers. The experiment also shows that the 4.5 × 105 spz/egg ratio is not sufficient for good fertilization, and it is necessary to use higher sperm concentrations per egg or improve the method of fertilization.
Keywords: Computer-assisted sperm analysis; Cryopreservation; Cypriniformes; Sperm concentration; Sperm motility; Sperm spectrophotometry